Multidisciplinary treatment with immune checkpoint inhibitors for advanced stage hepatocellular carcinoma - Ahlim Lee; Jaejun Lee; Hyun Yang; Soo-Yoon Sung; Chang Ho Jeon; Su Ho Kim; Moon Hyung Choi; Young Joon Lee; Ho Jong Chun; Si Hyun Bae (Korean Liver Cancer Association, 2022)
Hepatocellular carcinoma (HCC) is a cytotoxic chemotherapy-resistant tumor and most HCCs arise in a background of liver cirrhosis of various causes. Although the IMBrave150 trial showed remarkable advancements in the treatment of unresectable HCC with atezolizumab plus bevacizumab (AteBeva), therapeutic outcomes were unsatisfactory in more than half of the patients. Accordingly, many ongoing trials combine conventional modalities with new drugs such as immune checkpoint inhibitors for better treatment outcomes, and they are expected to benefit patients with limited responses to conventional treatment. Here, two patients with advanced stage HCC with preserved liver function and good performance status showed partial response after treatment with combination or sequential therapy of AteBeva, hepatic arterial infusion chemotherapy, radiation therapy, and transarterial chemoembolization. These findings indicate the efficacy of multidisciplinary treatment against advanced HCC. Additional studies are required to establish optimal treatment strategies.